2015
DOI: 10.1002/2014jd021812
|View full text |Cite
|
Sign up to set email alerts
|

Simulating diurnal variations over the southeastern United States

Abstract: The diurnal variations from a high-resolution regional climate model (Regional Spectral Model; RSM) are analyzed from six independent decade long integrations using lateral boundary forcing data from the National Centers for Environmental Prediction Reanalysis 2 (NCEPR2), European Center for Medium-Range Weather Forecasts 40-year Reanalysis and the Twentieth Century Reanalysis (20CR). With each of these lateral boundary forcing data, the RSM is integrated separately using two convection schemes: Relaxed Arakaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…This bias in the onset date of the wet season in the RCM simulations stem partly from the misrepresentation of the land cover type in the Everglades region as perennial ground cover [cf. Selman and Misra , , Figure 1] as swamp or saturated land mass type does not exist in the land surface model [ Ek et al ., ]. Furthermore, bias in the clouds and associated surface fluxes (not shown) and their consequent impact on bias of surface temperature, moisture flux convergence, and convection (shown later) also affect the onset date simulation in the RCM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This bias in the onset date of the wet season in the RCM simulations stem partly from the misrepresentation of the land cover type in the Everglades region as perennial ground cover [cf. Selman and Misra , , Figure 1] as swamp or saturated land mass type does not exist in the land surface model [ Ek et al ., ]. Furthermore, bias in the clouds and associated surface fluxes (not shown) and their consequent impact on bias of surface temperature, moisture flux convergence, and convection (shown later) also affect the onset date simulation in the RCM.…”
Section: Resultsmentioning
confidence: 99%
“…A brief outline of the physics of the RSM used in this study is provided in Table . The choice of these schemes stems from previous successful simulations over the region [ DiNapoli and Misra , ; Selman et al ., ; Selman and Misra , ].…”
Section: Methodology and Data Setsmentioning
confidence: 99%
“…Moreover, as the TP is the highest plateau in the world with low air density, model differences in DTR are significantly affected by clouds, long‐wave and short‐wave fluxes, consistent with the previous study (Lindvall and Svensson, ). Meanwhile, the DTR is the result of a complex interplay of many processes, involving the land surface and the atmospheric boundary layer as well as the atmosphere circulation (Lindvall and Svensson, ; Sayemuzzaman et al ., ; Selman and Misra, ). Cloud cover is important but other factors are also considered to explain a large proportion of the geographic variations in DTR (Jackson and Forster, ), and numerical models have underestimated the observed DTR decrease on the global scale, suggesting that the inadequate representation of model cloud cover leads to unrepresentative maximum/minimum temperature (Braganza et al ., ; Lauritsen and Rogers, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most GCMs are hardly able to simulate the interannual variations of DTR, and cannot reproduce the seasonal variations of observed DTR on the TP, which is related to the assimilation scheme for the maximum/minimum temperature. These findings are in general agreement with numerous analyses on the global and regional scales (Lewis and Karoly, ; Lindvall et al ., ; Cattiaux et al ., ; Lindvall and Svensson, ; Selman and Misra, ). It is shown that model bias for DTR is greater for winter than summer, which may be related to changes in snow cover (land surface property) and cloud that alter the albedo during the cool period of the year (You et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation